Identification of putative viroplasms within banana cells infected by banana streak MY virus. (1st December 2020) - Ngo, Thu Ha; Webb, Richard; Crew, Kathleen S.; Vance, Megan E.; Thomas, John E.; Geering, Andrew D. W.
Abstract : The badnavirus replication cycle is poorly understood and most knowledge is based on extrapolations from model viruses such as Cauliflower mosaic virus (CaMV). However, in contrast to CaMV, badnaviruses are thought not to produce viroplasms and therefore it has been a mystery as to where virion assembly occurs. In this study, ultrathin sections of a banana leaf infected with a badnavirus, banana streak MY virus (BSMYV), were examined by transmission electron microscopy. Electron-dense inclusion bodies (EDIBs) were sporadically distributed in parenchymatous tissues of the leaf, most commonly in the palisade and spongy mesophyll cells. These EDIBs had a characteristic structure, comprising an electron-dense core, a single, encircling lacuna and an outer ring of electron-dense material. However, much less frequently, EDIBs with two or three lacunae were observed. In the outer ring, densely packed virions were visible with a shape and size consistent with that expected for badnaviruses. Immunogold labelling was done with primary antibodies that detected the N-terminus of the capsid protein and strong labelling of the outer ring but not the central core or lacuna was observed. It is concluded that the EDIBs that were observed are equivalent in function to the viroplasms of CaMV, although obviously different in composition as there is not a paralogue of the transactivation/viroplasm protein in the badnavirus genome. It is postulated that production of a viroplasm could be a conserved characteristic of all members of the Caulimoviridae .